ACHIEVEMENT OF MPEG - 7 and MPEG - 21 AS STANDAERS FOR ACCESS, DISTRIBUTION AND MANAGEMENT WITH INFORMATION - Selim, Aybeyan; Grupchev, Vladimir (International Scientific Journal Vision, 2018)
Today, the Internet allows the spread and distribution of not only textual but also audio - visual data. The rapid development and increasing demand of these data, has led institutions that standardize this data and they create new technologies. However, the concept of enriching multimedia data and the increasing diversity of devices using multimedia networks has also led to some difficulties in managing these communications. As a result of such a growing demand of users, of the institutions and everyday needs of a modern man, MPEG - 7 and MPEG 21 standards have been developed. These standards provide more information on the content of multimedia data and consist of autonomous factors who have an expandable architecture. Multimedia systems provide information to users in different locations, a different form of data that can be accessed in different ways. This paper presents the areas in which MPEG - 7 and MPEG 21 standards are applied.